2007
DOI: 10.1124/dmd.106.014530
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of Prasugrel in Humans Using a Novel Chiral Liquid Chromatography-Tandem Mass Spectrometry Method

Abstract: ABSTRACT:A liquid chromatography-tandem mass spectrometry method was developed to chromatographically separate the four stereoisomers of the active metabolite of prasugrel, R-138727, in human plasma after derivatization with bromomethoxyacetophenone to stabilize the molecule. This technique was designed to determine the relative contribution of each stereoisomer, based on statistical analyses of each stereoisomer's chromatographic peak areas. The methodology was validated and used for the analysis of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…In humans, greater concentrations of the R-configuration at the 4-position of R-138727 (Wickremsinhe et al, 2007) were observed in plasma. This in vivo stereoselectivity may be explained in part by the observed in vitro stereoselectivity in the P450-mediated oxidation of the thiolactone to R-138727 by cDNA-expressed P450 isoforms (Rehmel et al, 2006;Baker et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, greater concentrations of the R-configuration at the 4-position of R-138727 (Wickremsinhe et al, 2007) were observed in plasma. This in vivo stereoselectivity may be explained in part by the observed in vitro stereoselectivity in the P450-mediated oxidation of the thiolactone to R-138727 by cDNA-expressed P450 isoforms (Rehmel et al, 2006;Baker et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…RR isomer .. SS isomer = SR isomer (Hasegawa et al, 2005). In humans, the pharmacologically active RS and RR isomers were detected in plasma at about 5-fold higher levels than the pharmacologically less active SS and SR isomers after dosing of prasugrel (Wickremsinhe et al, 2007). In rats, the RS and RR isomers were the major forms detected in plasma, and the SS and SR isomers were only detected at much lower concentrations in plasma (Kazui et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors demonstrated that the acidic and basic mobile phase additives can have a significant impact in addition to the classical factors such as temperature, pH and type of organic modifier, which can influence the enantio separation in LC (Matthijs et al, 2006, Perrin et al, 2002, Ye Y et al, 2001, Levin et al, 1993, Khatuna et al, 2015, Gübitz et al, 2006. These studies mostly carried by normal-phase chromatography, as these additives were supposed to minimize the non-specific interactions between the analytes and the free silanol groups of the CSP.…”
Section: Optimization Of Chromatographic Conditionsmentioning
confidence: 99%
“…One method discusses about Stereo selective Metabolism of Prasugrel in Humans Using a Novel Chiral Liquid Chromatography-Tandem Mass Spectrometry Method (Enaksha et al, 2007). Another work reveals about Electrospray ionization LC-MS/MS validated method for the determination of the active metabolite (R-138727) of prasugrel in human plasma and its application to a bioequivalence study (Ojikumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation